Scutellarin Suppresses Platelet Aggregation and Stalls Lesional Progression in Mouse With Induced Endometriosis. (November 2019) - Ding, Ding; Cai, Xianjun; Zheng, Hanxi; Guo, Sun-Wei; Liu, Xishi
Platelets play an important role in the development of endometriosis. Scutellarin is a flavonoid isolated from a medicinal herb traditionally used as a potent antiplatelet agent. In this study, we sought to evaluate its potential therapeutic effect, if any, in mice with induced endometriosis. Endometriosis was induced in 27 female Balb/c mice by intraperitoneal injection of uterine fragments. Two weeks after the induction, the 27 mice were randomly divided in equal sizes into 3 groups: untreated, which received only vehicle, and low-dose and high-dose groups, which received low- and high dose of scutellarin treatment. Hotplate test was administrated to all mice before endometriosis induction, and before and after the scutellarin treatment. Two weeks after the treatment, a blood sample was drawn before sacrifice and all lesions were harvested. The peripheral platelet activation rate and total lesion weight were assessed, and immunohistochemistry and histochemistry analyses were performed to evaluate the extent of proliferation, angiogenesis, fibroblast-to-myofibroblast transdifferentiation (FMT), and fibrosis in lesions. Compared with untreated mice, mice in both low-dose and high-dose groups had significantly reduced lesion weight and improved hyperalgesia. Scutellarin also reduced the peripheral-activated platelets rate and resulted in significantly reduced platelet aggregation, cellular proliferation, angiogenesis, the extent of FMT, and the extent of fibrosis in lesions. Thus, we conclude that scutellarin is efficacious in treating endometriosis in vivo by suppressing platelet aggregation, inhibiting proliferation, angiogenesis, and fibrogenesis, resulting in reduced lesion size and improved pain behavior. As such, scutellarin may be a potentially promising therapeutics for the treatment of endometriosis.